AN UNUSUAL PRESENTATION OF INFECTIVE ENDOCARDITIS - Abdullah, Layla; Allana, Saleema (Journal of Ayub Medical College Abbottabad, 2013)
This paper reports a case of a 22 years old young male who presented in emergency department with some non-specific symptoms such as abdominal pain, vomiting, chest heaviness and shortness of breath. Chest x-ray revealed a combined picture of pneumonia and congestive heart failure. Echocardiogram showed ventricular septal defect, aortic regurgitation and mitral stenosis. Later on diagnosed with infective endocarditis and the culprit was his native valves. He went through aortic valve replacement and discharged after full recovery. Keywords: Infective endocarditis, unusual presentation, valve replacement